Ionospheric response over Thailand from the 15 January 2022 eruption of the Hunga Tonga-Hunga Ha'apai volcano - Paparin Jamlongkul; S. Wannawichian; L. J. Paxton; Clayton Cantrall; Pornchai Supnithi; Jirapoom Budtho; Michi Nishioka; Thananphat Thanakulketsarat; Phimmasone Thammavongsy (My University, 2024)
This study reports on the upper atmospheric response over Thailand to the Hunga Tonga volcano’s eruption on January 15th, 2022. The eruption occurred during the geomagnetic storm recovery phase, providing a rare comparison between effects from outside
Keywords: Ionosphere and magnetosphere dynamics; Earthquake Detection and Analysis; GNSS positioning and interference